Human metallothionein genes: molecular cloning and sequence analysis of the mRNA. - Karin, M (1982)
From a cDNA clone bank prepared from cadmium-treated HeLa cells, we isolated clones representing mRNAs whose concentration is increased after cadmium induction. Several metallothionein cDNA clones were isolated by cross-hybridization to mouse metallothionein-I cDNA. The nucleotide sequence of one of these clones, containing a nearly full-length cDNA copy of human metallothionein-II mRNA, was determined. The homology between the human and mouse metallothionein sequences is strictly limited to the coding region of the mRNA. Codon usage in metallothionein mRNA is not random. Seventy-nine percent of the codons have G or C residues at the third position, resulting in a GC-rich sequence.